ANALISA PENGARUH PERLAKUAN ALKALI TERHADAP SIFAT MEKANIK KOMPOSIT BERPENGUAT SERAT BUAH KELAPA SAWIT - Sundari, Ella; Karmin, Karmin; Putri, Fenoria; Arif Budiman (Politeknik Negeri Sriwijaya, Indonesia, 2023)
Various innovations have been developed by researchers to obtain and develop new natural fibers because of its advantages. Some of the advantages of natural fibers such as excellent physical properties, abundant natural materials, do not damage the environment and lower production costs. This study aims to produce alternative natural fibers by utilizing fiber from oil palm fruit which is commonly found in South Sumatra. The research was carried out by preparing resin and catalyst with a ratio of 100 ml: 1 ml which was then poured into the mold as much as 25% and continued by arranging palm fruit fiber randomly. After 8 hours, the resulting composite material is soaked for 2 hours with NaOH alkaline liquid with variations of 0%, 5% and 7%. The mechanical properties of the palm fruit fiber composite increased after being treated with alkali, where the highest values ​​were tensile strength 22.46 N/mm2, impact strength 0.15 J/mm2 and bending strength 87.50 N/mm2 obtained at variations of alkaline NaOH of 7 %.